The Potential of Cancer Biomarkers and Biosensing Technology for Early Detection of Cancer: A Comprehensive Review - Sourav Das; Sukanta Roy; Anirbandeep Bose; Subhasish Mondal (Current Overview on Pharmaceutical Science Vol. 6, 2023)
Cancer detection in early stages may decrease the death rate as initial treatments may be employed which will minimise the chance of becoming metastasis. After some genes mutation few specific proteins and enzymes produced are over-expressed for different cancers, which are identical for different cancers. The presence of those specific bio-molecules and concentrations of those bio-molecules in biological sample, known as biomarkers can be an important tool in detecting cancer. Apart from the earlier detection techniques, a new detection trends has been employed in cancer research. Sensors for biological molecules i.e., optical, electrochemical, magnetic sensors are employed which provides digital signals against biological samples via different mechanisms. These bio sensing technologies enables cost effective, simple, sensitive outcomes, which minimises cancer detection complications. Herein this chapter will present, discussion of various biomarkers employed in detection cancers with new detection trends using biosensors of different mechanisms like microfluidic chips in smartphone, nano molecule based biosensors etc.